(845) A Guide for The Programmers & Operators on the I.B.M 1620 دليل للمبرمجين والمشغلين على جهاز I.B.M. 1620 - Abdel Aziz, Abdalla; El-Gohary, H. (The Institute of National Planning, 2024)
Part I contains operating procedures for the I.B.M. 1520 FØRTRAN II programming system, providing the necessary information for efficient use of FØRTRAN II. In addition to the operating procedures, this part includes a detailed description of error messages and restart procedures. Part II is a short note on the description of the FORTRAN II language, summarizing the main statements used to provide a clear view of the specifications. Part III contains selected examples of examination exercises, helping users understand the practical applications of the language.